2019
DOI: 10.1093/nar/gkz461
|View full text |Cite
|
Sign up to set email alerts
|

hnRNPC regulates cancer-specific alternative cleavage and polyadenylation profiles

Abstract: Alternative cleavage and polyadenylation (APA) can occur at more than half of all human genes, greatly enhancing the cellular repertoire of mRNA isoforms. As these isoforms can have altered stability, localisation and coding potential, deregulation of APA can disrupt gene expression and this has been linked to many diseases including cancer progression. How APA generates cancer-specific isoform profiles and what their physiological consequences are, however, is largely unclear. Here we use a subcellular fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 44 publications
6
90
0
Order By: Relevance
“…Several processes could be responsible, such as posttranscriptional modifications, protein degradation, secretion via exocytosis or alterations in subcellular protein localization. For example a recent paper has reported that NAP1L1 undergoes alternative cleavage and polyadenylation in the more advanced stages of CRC (38). The full length isoform of NAP1L1 was overrepresented in the cytoplasmic fraction of a CRC cell line which had a more metastatic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Several processes could be responsible, such as posttranscriptional modifications, protein degradation, secretion via exocytosis or alterations in subcellular protein localization. For example a recent paper has reported that NAP1L1 undergoes alternative cleavage and polyadenylation in the more advanced stages of CRC (38). The full length isoform of NAP1L1 was overrepresented in the cytoplasmic fraction of a CRC cell line which had a more metastatic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…12q24 chromosomal region gain tumours (where it is located) [112]. RAN also promotes AURKA activity, with Schnepp and colleagues suggesting that RAN overexpression could be targeted by aurora kinase inhibitors.…”
Section: Rbps Associated With High-risk Patient Death: Aff2 and Bard1mentioning
confidence: 99%
“…HNRNPC was ranked 30 in our Kaplan scan analyses. Overexpression of HNRNPC has a critical role in the establishment of alternative cleavage and polyadenylation profiles, which are characteristic of metastatic colon cancer cells [112]. Furthermore, the loss of HNRNPC strongly reduces the abundance of BRCA1, BRCA2, RAD51 and BRIP1 due to aberrant splicing effects [113].…”
Section: Rbps Associated With High-risk Patient Death: Aff2 and Bard1mentioning
confidence: 99%
See 1 more Smart Citation
“…The TAPA event introduces two or more poly(A) sites to the 3′ UTR of a gene which is distributed across a wide variety of cancers and modulates the sensitivity of certain anticancer drugs [12,13]. The shift of TAPA events shows a cancer-specific and cell organelle-specific mode [14]. It was reported that the APA-guided shortening of NET1 gene 3' UTR enhanced mRNA transcriptional activity and promoted the metastasis of gastric cancer cells [15].…”
Section: Introductionmentioning
confidence: 99%